2021
DOI: 10.1007/s10654-020-00712-6
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary behaviour in relation to ovarian cancer risk: a systematic review and meta-analysis

Abstract: Sedentary behaviour is an emerging risk factor for several site-specific cancers. Ovarian cancers are often detected at late disease stages and the role of sedentary behaviour as a modifiable risk factor potentially contributing to ovarian cancer risk has not been extensively examined. We systematically searched relevant databases from inception to February 2020 for eligible publications dealing with sedentary behaviour in relation to ovarian cancer risk. We conducted a systematic review and meta-analysis, cal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 50 publications
1
24
0
Order By: Relevance
“…For neoplasms, we only found suggestive evidence about the associations of sedentary time with lung, breast and endometrium cancer before multiple correction, which were generally similar to a recent review that sedentary time, independent of physical activity, has been shown to increase the risk of colon, endometrial, and lung cancers. 27 Previous studies also demonstrated no significant associations with multiple site-specific cancer, such as ovary, 28 prostate, 29 oesophago gastric, 30 colorectal cancer. 13 Moreover, a meta-analysis including 43 observational studies almost presented consistent associations between sedentary time and site-specific cancers.…”
Section: Discussionmentioning
confidence: 95%
“…For neoplasms, we only found suggestive evidence about the associations of sedentary time with lung, breast and endometrium cancer before multiple correction, which were generally similar to a recent review that sedentary time, independent of physical activity, has been shown to increase the risk of colon, endometrial, and lung cancers. 27 Previous studies also demonstrated no significant associations with multiple site-specific cancer, such as ovary, 28 prostate, 29 oesophago gastric, 30 colorectal cancer. 13 Moreover, a meta-analysis including 43 observational studies almost presented consistent associations between sedentary time and site-specific cancers.…”
Section: Discussionmentioning
confidence: 95%
“…For cancer incidence of individual sites, we included ten [ 7 9 , 11 , 35 , 49 53 ] meta-analyses with a total of 212,707 cancer cases and 17 different cancer sites from 77 individual studies (50 cohort and 27 case–control studies). Of those eleven meta-analyses, ten showed a statistically significant association with cancer incidence.…”
Section: Resultsmentioning
confidence: 99%
“…5 Increased BMI in childhood has been demonstrated to increase the likelihood of obesity in adulthood, 68 which in turn increases the risk of developing noncommunicable diseases. Sedentary behavior has been positively associated with increased risk of disease later in life, 69 including type 2 diabetes, 70 diabetic retinopathy, 71 cancer, [72][73][74] dementia, 75 and cardiovascular disease. 70 Low levels of physical activity, low cardiorespiratory fitness, and sedentary behavior are significantly associated with the development of metabolic syndrome.…”
Section: Risks Of Increased Digital Screen Timementioning
confidence: 99%